La spedizione in Bosnia del principe Eugenio di Savoia, 1697 - Nemeth, Gizella; Papo, Adriano (Études sur la Région Méditerranéenne, 2024)
After the conclusion of the victorious Zenta campaign, Prince Eugene of Savoy, unable to conquer Temesvár, organized a raid in the heart of Bosnia, even as far as the capital Sarajevo, a rich merchant city. The Bosnian expedition is described on the basis of various narrative and documentary sources. Prince Eugene personally led his expeditionary force with 4,000 of his best cavalry, 2,000-2,500 elite foot soldiers, 12 field guns, two mortars. He was accompanied by some of his best senior officers such as Count Guido von Starhemberg and Prince Charles of Lorraine-Commercy; he had entrusted the command of the vanguard to Colonel Kyba, who knew the area well, having served for a long time in the border militias. To distract the attention of the Turks from Bosnia, Eugene had commissioned the cavalry general Jean-Louis Rabutin de Bussy to make frequent diversions in the direction of Temesvár and along the Danube. The expedition lasted from 6 October 1697, when the prince left Eszék (Osijek), until 8 November, the day of his return to his starting point. During the expedition the prince traveled the country more or less along the Bosna River, crossing plains, narrow gorges, high and steep mountains, took a few castles, some of which put up resistance, and finally burned down the city of Sarajevo, the main square of the country, because the Turks had not respected the customs of war at the time: they had killed a messenger of the prince and seriously wounded another, who had gone to them to order surrender. The Christian people residing there welcomed the imperials lovingly, supplying them with food, and many of them joined Eugene’s troops following him back home. The intense cold and the early snow made the return journey particularly difficult.